1999
DOI: 10.1046/j.1365-2222.1999.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for the hepatobiliary system in IgE‐mediated intestinal inflammation in the rat

Abstract: The data indicate that biliary products are major contributors to the gastrointestinal damage arising from IgE-mediated hypersensitivity reactions in the rat, and such hypersensitivity reactions may involve a population of mast cells which reside in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…There are at least two types of mast cells, the mucosal type of mast cells (MMC) and the connective tissuetype of mast cells. In rats, staining of mast cells in liver sections with alcian blue/safranin indicates that these cells are predominantly of the mucosal subtype [18], with Collins and co-workers reporting that <7% of hepatic mast cells had the staining characteristics of connective tissue mast cells [20]. These MMC are the local source of large quantities of chemical mediators, including histamine [12,13], leukotrienes [21], and plateletactivating factor [22], which have been postulated to play important functions in the pathogenesis of I/Rinduced tissue injury.…”
Section: Discussionmentioning
confidence: 92%
“…There are at least two types of mast cells, the mucosal type of mast cells (MMC) and the connective tissuetype of mast cells. In rats, staining of mast cells in liver sections with alcian blue/safranin indicates that these cells are predominantly of the mucosal subtype [18], with Collins and co-workers reporting that <7% of hepatic mast cells had the staining characteristics of connective tissue mast cells [20]. These MMC are the local source of large quantities of chemical mediators, including histamine [12,13], leukotrienes [21], and plateletactivating factor [22], which have been postulated to play important functions in the pathogenesis of I/Rinduced tissue injury.…”
Section: Discussionmentioning
confidence: 92%
“…Not unreasonably, mast cells of the gastrointestinal tract have been implicated as the major effector cells in such reactions, 4 , 5 being ideally located at the site of inflammation and tissue damage. However, recent evidence suggests that the hepatobiliary system plays a crucial role in IgE‐mediated gastrointestinal hypersensitivity 6 . Although both hepatic and extrahepatic mast cells could account for the inflammatory mediators that have been detected in bile, the possible involvement of hepatic mast cells (HMC) highlights the need to better understand the nature and phenotype of these rarely studied cells.…”
Section: Introductionmentioning
confidence: 99%
“…showed that DBA/2 mice fed a continuous casein diet produced high level of casein‐specific IgE accompanied by an increase in Th2 cells in the liver 60 . Furthermore, mast cells that require IL‐4 for their survival and play an important role in IgE‐mediated hypersensitivity develop in the liver after feeding an Ag 61 . More importantly, a report has described a case in which a peanut allergy was transferred to the recipient of a donor liver, but not to the recipient of the kidney and pancreas of the same donor 62 .…”
Section: Portal Vein Tolerance and Food Allergymentioning
confidence: 99%